How Memory Structures Influence Distress and Recovery - Dobbin, Alastair; Ross, Sheila (Frontiers in Psychiatry, 2019)
The treatment of emotional distress has stalled. There has been no improvement in depression outcomes for 30 years and recent opinions have highlighted the lack of clear validity for the mechanisms involved in current models of complex psychological interventions. Emotional distress is a phenomenon that underpins a swathe of apparently diverse mental health conditions. Childhood trauma has been found to be endemic, and common in those with poor psychological adjustment in adults. Executive processes cause a split between knowledge of an event and knowledge of its negative ongoing emotional effects so making integration of the memory of such events and resolution of its effects a challenge. Recent research into the relationship between wellbeing and memory structures has converged with research into episodic memories and their key role in goal programming, giving an opportunity to describe a new model of with plausible mechanisms for emotional distress, regulation, resilience, and recovery. Humans seek goals that fulfil their universal basic psychological need for self-determination, and the structures of memory networks drive behavioural algorithms that can satisfy or thwart that goal. We propose that a single underlying deficit in memory networks could underpin the psychopathology of emotional distress and that a new formulation of distress and recovery could drive a useful update on the mechanisms of psychological interventions with greater validity and utility for recovery and propose the NEMESIS (NEgative MEmorieS Integration Systems) model.